Determinants Of The Purchasing Behavior Of Syrian Consumers In Light Of The War (A Field Study In The City Of Lattakia) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The importance of the consumer lies in the role he plays in the activity of any organization that provides its products to him. Successful marketing strategies depend on a deep understanding of the dimensions of the purchasing behavior of consumers and their constantly changing needs, especially in emergency conditions such as the current war in the country, where it imposed data that did not previously exist in the Syrian market. Such as the great change in prices and the variation in the level of quality in addition to the low purchasing power and other things, which put the Syrian consumer in front of a large number of options that may create difficulties for him in making the purchasing decision according to what satisfies his needs and renewed desires, and therefore we have prepared this research aimed at clarifying the most important Factors that affect the purchasing behavior of consumers and push them to make the purchasing decision in light of the war This research was applied to a random sample of residents of the city of Lattakia, and a set of conclusions and recommendations were reached, including: identifying new behavioral patterns and alternatives available to the consumer in light of crises, paying attention to the different economic levels of consumers and segmenting the market based on them, researching sources of information and experiences that Consumers have acquired them because of their impact on their choices and priorities, and thus affect their purchasing decision.